Neutrophils in the hepatocellular carcinoma microenvironment: orchestrators of progression and immunity - Lian, Yanjie; Wang, Li; Wang, Jiuchong; Zhu, Dan; Lyu, Wenliang (Frontiers in Immunology, 2026)
Among all malignant tumors, liver cancer is highly common, and hepatocellular carcinoma (HCC) stands as its most frequently seen pathological form. The majority of HCC patients are difficult to be detected or treated at an early stage. Concurrently, the postoperative recurrence rate remains relatively high, leading to a poor clinical prognosis of HCC. Recently, immunotherapy has made it promising to treat HCC. tumor microenvironment (TME) matters considerably in HCCprogression and metastasis. Neutrophils belong to the innate immune system’s essential elements, and their role as key regulators in the HCC-TME is becoming more widely recognized. By studying neutrophils ‘ pro-tumor and anti-tumor mechanisms in HCC, it is expected to gain a deeper comprehension of the functions of neutrophils and further reveal their biological characteristics. In addition, we analyze the crosstalk between neutrophils and other cellular constituents of the TME, and discuss emerging therapeutic strategies that target neutrophil-centric pathways. A deeper understanding of neutrophil biology will both illuminate the complexity of immune networks in liver cancer and offer a theoretical framework for HCC prevention and treatment.